1998
DOI: 10.1089/hyb.1998.17.463
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Immunosuppressive Anti-CD40 Ligand Monoclonal Antibody

Abstract: The interaction between CD40 ligand (CD40L) and its counter-receptor CD40 is critically important in T- and B-cell costimulation and generation of the humoral immune response. But several questions still remain unsolved, particularly in the human in vivo system. To clarify the precise function of CD40L and develop an immunosuppressive agent, we have generated a murine monoclonal antibody (MAb), 2B2 specific for human CD40L. The specificity of this MAb for human CD40L was verified by enzyme-linked immunoadsorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The HuPBL/SCID mouse Model #2 h as been effectively utilized to study the role of co-stimulatory molecules CD28, CD80, CD86, CD40 and CD154 in the development of human immune responses against allo-and xeno-antigens (55,56,(152)(153)(154). On the other hand, very few studies have been done in Model #2 to investigate the role of co-stimulatory molecules in tumor immunity.…”
Section: Co-stimulatory Molecule-based Immunotherapiesmentioning
confidence: 99%
“…The HuPBL/SCID mouse Model #2 h as been effectively utilized to study the role of co-stimulatory molecules CD28, CD80, CD86, CD40 and CD154 in the development of human immune responses against allo-and xeno-antigens (55,56,(152)(153)(154). On the other hand, very few studies have been done in Model #2 to investigate the role of co-stimulatory molecules in tumor immunity.…”
Section: Co-stimulatory Molecule-based Immunotherapiesmentioning
confidence: 99%
“…Studies originally identified CD40 on B lymphocytes, where it was shown to mediate T cell-dependent B cell activation and differentiation. It is found on most immune and some non-immune cells including macrophages, dendritic cells, endothelial cells, smooth muscle cells, and B cells, as well as astrocytes and microglia [5,1015]. Membrane-bound CD40 and its cognate CD40 ligand (CD40L–also known as CD154), a trimeric 33-kDa type II membrane glycoprotein, play a critical role in microglial phenotypic transformation from a ramified (resting), to an activated macrophage morphology [16] and enhance surface expression of inflammatory markers [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Landmark studies originally identified CD40 on B lymphocytes, where it was shown to mediate T-cell-dependent B-cell activation and differentiation. It is found on most immune and some nonimmune cells, including macrophages, dendritic cells, endothelial cells, smooth muscle cells and B cells, as well as astrocytes and microglia (9)(10)(11)(12)(13)(14)(15). CD40-L, also known as CD154, is a trimeric 33-kDa type II membrane glycoprotein that is predominantly expressed by activated T and B cells, astrocytes and platelets (13,16,17).…”
Section: Introductionmentioning
confidence: 99%